Bradycardia-to-Delivery Interval and Fetal Outcomes in Umbilical Cord Prolapse. Issue 6 (June 2021) - Wong, Lo; Tse, Wing T.; Lai, Chit Y.; Hui, Annie S. Y.; Chaemsaithong, Piya; Sahota, Daljit S.; Poon, Liona C.; Leung, Tak Y.
Abstract : (Abstracted from Acta Obstet Gynecol Scand 2021;100:170–177) Umbilical cord prolapse can lead to significant perinatal complications, including fetal hypoxia and birth asphyxia. In these cases, prompt delivery is required to preserve the life of the fetus and to reduce the risk of brain injury.